Analysis of hybrid combining ability for growth and multiple stress tolerance traits in the Pacific white shrimp, Litopenaeus vannamei - Wang, Lun; Liu, Jianyong (Frontiers in Animal Science, 2022)
To identify optimal mating combinations of the Pacific white shrimp, Litopenaeus vannamei, 47 combinations of the F1 generation were constructed by incomplete diallel crosses of six parental populations with different genetic backgrounds. A linear mixed model was used to estimate the general combining ability (GCA) and specific combining ability (SCA) for growth and multiple stress tolerance [high salt (35), low pH (6 ± 0.1, and high ammonia nitrogen (70 mg/L) co-stress] traits in the 47 combinations of L. vannamei at adult stage 105. The results showed that SCA in the parents had a dominant role in offspring traits. The highest GCAs were observed for females of strain O and males of strain B (0.602 and 8.889, respectively), indicating that dams of strain O and sires of strain B could be used as maternal and paternal lines to increase multiple stress resistance in the next generation. The growth traits of the hybrid combination strain G♂ × strain H♀ showed the highest degree of heterosis [body weight (BW) (46.518%), total length (TL) (15.288%), body length (BL) (15.214%), carapace length (CL) (9.838%), carapace width (CW) (10.964%), and abdomen length (AL) (17.116%)] and generally high SCA [BW (2.572), TL (8.596), BL (7.648), CL (1.328), CW (0.643), AL (6.344)] among all mating combinations. The SCA was highest for strain N♂ × strain O♀ multiple stress tolerance (30.131), while heterosis for that combination strain was third highest. Therefore, the combinations of strain G♂ × strain H♀ and of strain N♂ × strain O♀ can be used as candidate combinations for rapid growth and multiple stress tolerance, respectively. This study provided useful data for growth and stress resistance breeding in L. vannamei; it also provided reference materials for growth and breeding to achieve multiple stress resistance.